1982
DOI: 10.1136/jnnp.45.12.1130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of damage to the central nervous system by determination of S-100 protein in the cerebrospinal fluid.

Abstract: SUMMARY S-100 protein was determined by Particle Counting ImmunoAssay in the CSF of patients with various neurological disorders. With a limit of sensitivity of 2 5 ,ug/l this brain-specific protein was detected only in samples from patients with acute damage of the central nervous system, particularly in compression of the spinal cord by tumour, ischaemic disorders, subarachnoid bleeding and haematoma, and viral or suspected viral infections. Our results support the assumption that S-100 is a reliable index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…The reference range found for CSF (< 2.4 g/l) corresponds well with the values reported in the literature (7,13,21). Several factors may contribute to the clear differences between the reference values for blood reported by Persson et al (9) and those reported in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reference range found for CSF (< 2.4 g/l) corresponds well with the values reported in the literature (7,13,21). Several factors may contribute to the clear differences between the reference values for blood reported by Persson et al (9) and those reported in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of calcium on the measurement of S-100 protein has already been described by Sindic et al (13). We found the same optimal calcium concentration as Sindic et al, and the addition of 5 mmol/1 CaCl 2 decreased the lower detection limit of our assay.…”
Section: Discussionsupporting
confidence: 86%
“…However, in this study, the correlation between the size of the ischemic area and the astroglial protein increment apparently was not investigated, and no correlation to the clinical outcome of these patients was found. 5 Even so, in studies concerning other cerebral disorders, such as herpes encephalitis 22 and subarachnoid hemorrhage, 23 -24 the S-100 concentration was found to be related to the clinical state, as well as to the outcome of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…4 Increased CSF and plasma levels of S100B have been detected after traumatic brain injury, toxic or ischemic brain damage, and in multiple sclerosis. [8][9][10][11][12][13][14][15][16][17] S-100B is also elevated in several kinds of dementia, especially Alzheimer's disease. 5 Our group showed increased S-100B plasma levels in medicated patients suffering from schizophrenia, 18 whereas Gattaz and colleagues reported decreased S100B concentrations in medicated patients with schizophrenia.…”
mentioning
confidence: 99%